A novel approach to wireless electromagnetic tracking using frequency modulation radio communication - Crowley, Daragh; Cavaliere, Marco; Cantillon-Murphy, Pádraig (International journal for computer assisted radiology and surgery, 2023)
Purpose Electromagnetic tracking (EMT) is beneficial in image-guided interventions to reduce the use of ionising radiation-based imaging techniques. Enabling wirelessly tracked sensors will increase the usability of these systems for catheter tracking and patient registration systems. This work introduces a novel method of wirelessly transmitting sensor data using a frequency modulation (FM) radio. Methods The proposed technique was tested using the open-source Anser EMT system. An electromagnetic sensor was connected in parallel to an FM transmitter prototype and wired directly to the Anser system for comparison. The performance of the FM transmitter was evaluated on a grid of 125 test points using an optical tracking system as a gold standard. Results An average position accuracy of 1.61 ± 0.68 mm and angular rotation accuracy of 0.04° for the FM transmitted sensor signal was obtained over a 30 cm × 30 cm × 30 cm volume, in comparison with the 1.14 ± 0.80 mm, 0.04° accuracy previously reported for the Anser system. The FM transmitted sensor signal had an average resolved position precision of 0.95 mm while the directly wired signal was found to have an average precision of 1.09 mm. A very low frequency ( ∼ 5 mHz) oscillation in the wirelessly transmitted signal was observed and compensated for by performing a dynamic scaling of the magnetic field model used for solving the sensor pose. Conclusions We demonstrate that FM transmission of an electromagnetic sensor signal can be used to achieve similar tracking performance to a wired sensor. FM transmission for wireless EMT is a viable alternative to digital sampling and transmission over Bluetooth. Future work will create an integrated wireless sensor node using FM communication that is compatible with existing EMT systems.